PERBEDAAN PENGHINDARAN PAJAK ANTARA PERUSAHAAN GRUP DAN NON GRUP - Fridian, Sonny Agus; Kamaludin, Kamaludin; Suranta, Eddy (UNIB Press, 2017)
This purpose of this study was experince the difference tax avoidance between group companies and non-group companies on non-financial companies listed on the Indonesian Stock Exchange (BEI) period 2011-2015, sample in this study amounted to 41 companies. The analysis method used is a mathematical calculation, then the variables have been calculated processed by using SPSS. This study found that there are no differences in tax avoidance between group companies and non-Group companies. Furthermore, this study found that non-group companies are more aggressive in tax planning than a group company.